Aggressive and Defensive Behaviour, Normative, and Social Adjustment in the Complex Dynamics of School Bullying - Manuel Carmona-Rojas; Rosario Ortega-Ruiz; Eva Romera; Ana Bravo (Psychosocial Intervention, 2023)

(untitled)
Bullying is a group phenomenon in which schoolchildren take on different roles. Although certain contextual elements play a key role in its evolution, very few longitudinal studies have been carried out to date which investigate how these factors interact. This study aims to explore the different class groupings as regards bullying norms and to examine the effect of the type of norm, social, and normative adjustment and pro-sociality, also of the interaction of group norms with involvement in aggression and victim defence in bullying situations. A total of 3,358 secondary school students (50.71% girls, Mage = 13 years, SD = 1.34) participated in the study. Four groups of norms towards bullying were identified: anti-bullying, anti-bullying but not actively defending, indifference, and pro-bullying. Univariate linear regression models showed that normative adjustment and the type of norms had a direct inverse effect on both types of behaviour, while pro-sociality only had an effect on defence. In groups with pro-bullying norms, a greater effect of normative adjustment was observed for involvement in defence and aggression, and pro-social skills were associated with aggression. These results suggest the need to work on moral, social and emotional elements to improve school climate in schools.